Plan de manejo residuos sólidos, sede Guanacaste, Universidad Técnica Nacional (UTN) - Arias-Alfaro, María (Instituto Tecnológico de Costa Rica, 2016)
This research was conducted to design a Comprehensive Management Plan for Solid Waste enclosure rods headquarters Guanacaste National Technical University. Located (length: - 85.08508 latitude: 10.43064 EPSG: 4326) in an area with an area of 2.5 ha (xmin .: -85.0859, 10.4295 .: ymin; xmax .: -85.0843, ymax .: 10.4317). The methodology used was to develop the baseline on the integrated management of solid waste where the generalities of the enclosure described, a description of the state at the time of fieldwork research solid waste management and a study was conducted quantification generation and composition thereof. In addition, alternatives for proper treatment of solid waste were evaluated from technical, environmental and economic perspective and with all inputs obtained Plan Solid Waste Management programs, projects, goals, indexes, and other materialized. The aim is to present the plan to the Council of Headquarters premises Corobicí UTN Guanacaste headquarters and approved to run and so the institution meets Costa Rican law and abide by the law for Waste Management (8839).

Esta investigación se realizó para diseñar un Plan de Gestión Integral de Residuos Sólidos para el recinto de Cañas de la sede Guanacaste en Universidad Técnica Nacional. Ubicado (longitud: -85.08508, latitud: 10.43064 EPSG: 4326) en un predio con una extensión de 2.5 ha (xMín.: -85.0859, yMín.: 10.4295; xMáx.: -85.0843, yMáx.: 10.4317). La metodología utilizada consistió en elaborar la Línea Base sobre la gestión integral de los residuos sólidos donde se describieron las generalidades del recinto, se realizó una descripción del estado al momento del trabajo de campo de la investigación del manejo de residuos sólidos y un estudio de la cuantificación de generación y composición de los mismos. Además, se evaluaron las alternativas para el tratamiento adecuado de los residuos sólidos desde la perspectiva técnica, ambiental y económica y con todos los insumos obtenidos se concretó el Plan de Manejo de Residuos Sólidos con programas, proyectos, metas, índices, y demás. El fin es presentar el Plan al Consejo de Sede del recinto Corobicí de la UTN sede Guanacaste y sea aprobado para que se ejecute y así la institución cumpla con la normativa costarricense y acate la ley para la Gestión Integral de Residuos (8839).
Proyecto de Graduación (Maestría en Gerencia de Recursos Naturales y Tecnologías de Producción) Instituto Tecnológico de Costa Rica, Área Académica Agroforestal, 2016.
Keywords: Eficiencia; Desechos; Planeamiento; Tratamiento; Research Subject Categories::NATURAL SCIENCES::Biology::Terrestrial, freshwater and marine ecology::Terrestrial ecology